Estimating the rate and determinants of exclusive breastfeeding practices among rural mothers in Southern Ghana - Alfred Kwesi Manyeh; Alberta Amu; David Etsey Akpakli; John E. Williams; Margaret Gyapong (BMC, 2020)
Abstract Background The health benefits of exclusive breastfeeding practices in both the short and long term accrue to breastfed infants, mothers, families and the society at large. Despite the evidence of these benefits and adoption of various World Health Organization (WHO) strategies on promotion of exclusive breastfeeding by Ghana, the increase in the rate of exclusive breastfeeding has been very slow in the country. This study aimed to estimate the rate and investigate socio-economic and demographic determinants of 6 months exclusive breastfeeding in two rural districts in Southern Ghana. Methods Pregnancy, childbirth, breastfeeding, demographic and socioeconomic information of 1870 women who were prospectively registered by the Dodowa Health and Demographic Surveillance System and gave birth between 1 January 2011 and 31 December 2013 was extracted. The proportion of 6 months exclusive breastfeeding among the study participants was estimated and the relationship between the dependent and the independent variables were explored using logistics regression model at 95% confidence level. Results The proportion of mothers who exclusive breastfed for 6 months in the study was 71.0%. Mothers aged 25-29 and 30 + years are 93 and 91% respectively more likely to practice 6 months exclusive breastfeeding compared to those aged < 20 years (OR 1.93, 95% CI 1.25, 2.99, OR 1.91, 95% CI 1.91, 3.08). The odds of artisan mothers practicing 6 months exclusive breastfeeding is 36% less likely compared to those unemployed (OR 0.64, 95% CI 0.43, 0.96). There is a higher chance that 45% of mothers with a household size of more than five members to practice exclusive breastfeeding compared to those with household size of less than six (OR 1.45, 95% CI 1.16, 1.81). Women in the fishing district were 85% less likely to practice 6 months exclusive breastfeeding compared to those in farming district (OR 0.15, 95% CI 0.12, 0.20). Conclusion There is high rate of exclusive breastfeeding in the study area. Maternal age, type of occupation, household size and district of residence are determinants of 6 months exclusive breastfeeding among the study participants.